2023
DOI: 10.18502/jri.v24i1.11906
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Increment of Interleukin-1 and Interleukin-6 in Women with Polycystic Ovary Syndrome and Body Mass Index

Abstract: Background: There is an association between inflammatory factors and polycystic ovary syndrome (PCOS) and most of women with PCOS experience the symptoms of hirsutism. The purpose of this study was to evaluate the role of obesity in PCOS occurrence, which is linked with inflammation and hirsutism. Methods: This study was designed as a case-control research. It was performed on 102 women with PCOS and 102 healthy women as controls who were age-matched. Serum concentrations of testosterone, estradiol (E2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Our data on the increase in pro-inflammatory parameters in PCOS are consistent with previous studies of such parameters as IL-1α, IL-18, and IL-8 [39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Our data on the increase in pro-inflammatory parameters in PCOS are consistent with previous studies of such parameters as IL-1α, IL-18, and IL-8 [39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Its pathophysiology has not been well characterized, but various mechanisms, including endoplasmic reticulum (ER) stress ( Harada, 2022 ; Koike et al , 2023 ), oxidative stress ( Zeber-Lubecka et al , 2023 ), and abnormal inflammation and immunity ( Lima et al , 2018 ) have been implicated. Women with PCOS have high serum concentrations of pro-inflammatory molecules, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, and IL-18 ( Kaya et al , 2010 ; Alissa et al , 2021 ; Mazloomi et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA expression for the inflammatory mediators such as tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β) increased in the ovarian granulosa cells of PCOS patients compared to women without the condition [9]. Furthermore, previous studies have observed elevated IL-1β and IL-6 levels in the serum of PCOS subjects compared to the general population [10][11][12]. In contrast, previous research has shown that the reduction of PCOS-related symptoms is accompanied by a corresponding decrease in levels of inflammatory-related variables [13,14].…”
Section: Introductionmentioning
confidence: 99%